2014
DOI: 10.1002/ece3.1285
|View full text |Cite
|
Sign up to set email alerts
|

A grass–fire cycle eliminates an obligate‐seeding tree in a tropical savanna

Abstract: A grass–fire cycle in Australian tropical savannas has been postulated as driving the regional decline of the obligate-seeding conifer Callitris intratropica and other fire-sensitive components of the regional flora and fauna, due to proliferation of flammable native grasses. We tested the hypothesis that a high-biomass invasive savanna grass drives a positive feedback process where intense fires destroy fire-sensitive trees, and the reduction in canopy cover facilitates further invasion by grass. We undertook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 53 publications
2
66
0
1
Order By: Relevance
“…Selection pressure by crown fire regimes may have given rise to serotiny in the Callitris clade (Ladd et al, 2013) because they are extremely vulnerable to canopy defoliation by fire, given a very limited epicormic response. Many Australian species, however, have highly insulating bark that protects the cambium from high temperatures (Lawes et al, 2011;Bowman et al, 2014), consistent with adaptation to surface fire regime (Keeley, 2012). Although a previous study reported that C. sulcata has thin bark, which renders it vulnerable to fire (Ladd et al, 2013), we found that bark thickness of C. sulcata trees reached a plateau of 10 mm at a diameter of around 15 cm.…”
Section: Fire Recovery and Regeneration Strategiessupporting
confidence: 57%
See 3 more Smart Citations
“…Selection pressure by crown fire regimes may have given rise to serotiny in the Callitris clade (Ladd et al, 2013) because they are extremely vulnerable to canopy defoliation by fire, given a very limited epicormic response. Many Australian species, however, have highly insulating bark that protects the cambium from high temperatures (Lawes et al, 2011;Bowman et al, 2014), consistent with adaptation to surface fire regime (Keeley, 2012). Although a previous study reported that C. sulcata has thin bark, which renders it vulnerable to fire (Ladd et al, 2013), we found that bark thickness of C. sulcata trees reached a plateau of 10 mm at a diameter of around 15 cm.…”
Section: Fire Recovery and Regeneration Strategiessupporting
confidence: 57%
“…Although a previous study reported that C. sulcata has thin bark, which renders it vulnerable to fire (Ladd et al, 2013), we found that bark thickness of C. sulcata trees reached a plateau of 10 mm at a diameter of around 15 cm. Although this is substantially thinner than bark of C. intratropica trees (15 mm for trees with mean DBH of 21 cm), which grow in north Australian savannas subject to frequent surface fires (Bowman et al, 2014), it is thicker than that of Callitris macleayana (4.4 mm for trees with mean DBH of 20 cm), which grows in infrequently burnt Queensland rainforest (Lawes et al, 2011). It is therefore possible C. sulcata has evolved to tolerate infrequent surface fires.…”
Section: Fire Recovery and Regeneration Strategiesmentioning
confidence: 98%
See 2 more Smart Citations
“…This system provides an opportunity to examine the relative importance of shrub-grass interactions and other environmental controls on the balance of herbaceous and woody plants. An understanding of the strength of these determinants will provide insight into the way in which fuels and fire regimes are determined by community composition (Bowman et al 2014).…”
Section: Introductionmentioning
confidence: 99%